Significant enhancement of visible light photocatalytic activity of the hybrid B12-PIL/rGO in the presence of Ru(bpy)32+ for DDT dehalogenation. Issue 31 (31st March 2017) - Sun, Ying; Zhang, Wei; Tong, Jian; Zhang, Yu; Wu, Shuyao; Liu, Daliang; Shimakoshi, Hisashi; Hisaeda, Yoshio; Song, Xi-Ming
Abstract : A new hybrid catalyst, B12 -PIL/rGO, was prepared. It exhibited enhanced photocatalytic activity for DDT dechlorination in the presence of Ru(bpy)3 2+ . Abstract : A new B12 -PIL/rGO hybrid was prepared successfully through immobilizing a B12 derivative on the surface of poly(ionic liquid) (PIL)-modified reduced graphene oxide (rGO) by electrostatic attraction and π–π stacking attraction among the different components. The hybrid catalyst showed an enhanced photocatalytic activity in the presence of Ru(bpy)3 2+ for 1, 1-bis(4-chlorophenyl)-2, 2, 2-trichloroethane (DDT) dechlorination with ∼100% conversion. Especially, the yield of didechlorinated products could reach 78% after 1 h of visible light irradiation, which should be attributed to a synergistic effect of B12, rGO and PIL in B12 -PIL/rGO, including their respective catalytic performance, the excellent electron transport of rGO and the concentration of DDT and 1, 1-bis(4-chlorophenyl)-2, 2-dichloroethane (DDD) on the surface of B12 -PIL/rGO. Furthermore, the hybrid catalyst was easily recycled for use without obvious loss of catalytic activity.